PENDAMPING PENERAPAN SAK ETAP DALAM PENYUSUNAN LAPORAN KEUANGAN UNTUK PENINGKATAN POTENSI DESA MELALUI PRODUKTIVITAS PEMBANGUNAN SUMBER DAYA AIR BERSIH BUMDESA SUMBER BARU, DESA BANDAR BARU - Sipahutar, Tetty Tiurma Uli; Nainggolan, Benny Rojeston Marnaek; Romy, Elly; Piter, Jhon (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2024)
With the enactment of Law No. 6 of 2014, villages have become autonomous regions and have the right to manage their village income independently. Sumber Baru is a BUMDes in Deli Serdang Regency, Bandar Baru District, which emerged from village autonomy to realize the welfare of residents. The obligation of BUMDes as a legal entity to implement accounting standards has not been implemented in almost all regions in Indonesia. The purpose of this activity is to improve the knowledge and skills of BUMDesa administrators, especially in recording and preparing BUMDesa financial reports. The method used is training in recording and preparing BUMDesa financial reports using lecture techniques, tutorials, discussions (brainstorming), and post-training/mentoring. The results of the activities obtained are increased knowledge and understanding related to the accounting system starting from input in the form of transaction recording to the output produced in the form of BUMDesa financial reports containing financial information that will be used by BUMDesa stakeholders.